Study of Efficacy Adsorption of Methyl Green by Attapulgite and Modified Attapulgite Clay from Aqueous Solution - Jawad, Hussein; Mohammed Abbas, Ahmed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
This paper includes the modification of the attapulgite by precipitation of iron and aluminum compounds . Attapulgite (Atta) and modified attapulgite (Atta-m) clays are characterized by many techniques ( FTIR , XRD ,SEM with EDX ) .The attapulgite clay before and after modification were used as the adsorbents for adsorption of methyl green (MG) . The results Indicate ,that the percentage of removal (MG) at equilibrium by using (Atta) and (Atta-m) clay were reached to 94% and 97% respectively. Indicating that the clay modification process was in addition to a relative improvement in the adsorption potential of the clay after modification.